Can Sensory- and Attachment-Informed Approaches Modify the Perception of Pain? An Experimental Study - Pamela Joy Meredith; Nicole Emma Andrews; Jessica Thackeray; Sophie Bowen; Cory Poll; Jenny Strong (Pain Research and Management)
Accumulating evidence linking pain with both attachment and sensory processing variables introduces the possibility that attachment- and sensory-informed strategies may modify pain experiences. The aim of this study was to investigate this proposition using an experimentally induced pain procedure. Pain perceptions of individuals using either a sensory-informed (weighted modality) or an attachment-informed (secure base priming) coping strategy were compared with those of individuals using no designated coping strategy. An independent measures experimental study design was used with a convenience sample of 272 pain-free adults. Experimental participants (n = 156) were randomly allocated to either an attachment (n = 75) or a sensory (n = 81) intervention group. Data from these participants were compared to those of 116 participants involved in an earlier cold pressor study in which no coping strategy was used. All participants completed the same sensory, attachment, and distress questionnaires and participated in the same cold pressor pain test. ANCOVAs revealed that participants in the sensory- and attachment-informed intervention groups reported significantly higher pain thresholds than the control group. Participants allocated to the sensory group also reported higher pain intensity scores than the control group. There were no significant differences in pain tolerance between the three groups after controlling for covariates. While further research is required, findings encourage further consideration of sensory- and attachment-informed strategies for people anticipating a painful experience.